Comparison of different methods of managing bluestem pasture. - Smith, E.F.; Anderson, K. (Kansas Agricultural Experiment Station, 2012)
In the present serious the first test to compare different methods of grazing bluestem pasture was conducted in 1949 and was reported in Kansas Agricultural Experiment Station Circular 265. This report is concerned with the second test conducted in 1950. The objective of this experiment is to find out what the carrying capacity of bluestem pasture is, how deferred and rotation grazing compare with season long grazing, and if bluestem pasture should be burned or not.
Keywords: Beef; Stocking rate; Bluestem pasture